The Qur’an - Syed Asim Ali (International Institute of Islamic Thought, 2008)
Given that each teaching of the Qur’an is essential, it is neither possible nor desirable to divide its teachings into “essential,” “less-essential,” or “nonessential.” Since this book seeks to serve “the needs of those new to the study of the Qur’an,” The Qur’an: Some Essential Teachings would have been a more accurate title and would have forewarned the reader that the author presents only select teachings. That aside, A. R. Kidwai, a rising Islamic scholar, felt compelled to write this book to meet the needs of the common reader, because he believes that the available material mainly addresses the specialized reader. This brilliant work is designed to equip readers with the necessary tools to “grasp better advanced works on the Qur’an” (p. vi). The book mainly deals with the concepts of God, messengership, and the Hereafter and throws some light on modes of worship, as well as on social and family relations, in a very lucid, fluent, and persuasive manner. This book opens by analyzing the Qur’anic concept of God. The third chapter, which deals with the Prophet, is full of remarkable observations about his life and his role as a perfect role model for humanity. Some important aspects of his personality, however, have been left out, such as his leadership, emphasis on acquiring `ilm (knowledge), and the use of reason ...